TuBaFrost 2: Standardising tissue collection and quality control procedures for a European virtual frozen tissue bank network. - Morente, M; Mager, R; Alonso, S; Pezzella, F; Spatz, A; Knox, K; Kerr, D; Dinjens, W; Oosterhuis, J; Lam, K; Oomen, M; van Damme, B; et al. (2006)
Tumour Bank Networking presents a great challenge for oncological research as in order to carry out large-scale, multi-centre studies with minimal intrinsic bias, each tumour bank in the network must have some fundamental similarities and be using the same standardised and validated procedures. The European Human Frozen Tumour Tissue Bank (TuBaFrost) has responded to this need by the promotion of an integrated platform of tumour banks in Europe. The operational framework for TuBaFrost has drawn upon the best practice of standard workflows and operating procedures employed by members of the TuBaFrost project and key initiatives worldwide.